(untitled) (MMIT Proceedings, 2025)
This article provides an in-depth analysis of the didactic potential of distance learning platforms built on cloud technologies. The role and importance of cloud technologies in the educational process are evaluated, particularly in the context of changes that emerged during the pandemic. Distance learning platforms, supported by cloud technologies, offer opportunities to make the educational process more efficient and convenient. These platforms provide pedagogical advantages such as interactivity, flexibility, individualization, and the ability to function in multi-user environments. Interactivity, for instance, enables real-time communication between students and teachers, making the learning process more dynamic and engaging. Flexibility allows students to study at their own pace and according to their circumstances, which is especially important for those who have to balance education and work under various conditions. Individualization provides opportunities to tailor education according to each learner’s unique needs and abilities, thereby enhancing student motivation and improving the quality of education. The development model proposed in this article is recommended for the effective use of the didactic potential of cloud technologies. Based on this model, the role of cloud technologies in organizing more efficient distance learning and their importance for the quality of education is substantiated. As a result, the possibilities for making the learning process more effective and of higher quality through the integration of cloud technologies into education are examined. Furthermore, the article also analyzes new opportunities and challenges that may arise in the educational process through the use of cloud technologies. This is of significant importance for teachers and educational institutions in developing new strategies and enhancing the quality of education. Modernizing the educational process through cloud technologies plays a crucial role in promoting students’ self-development and improving the overall quality of learning.